Small-scale freshwater fish farming - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Handbook on small-scale freshwater fish farming FAO Training Series 24 1994 205pp ISSN 0259 2533